Legal Politics and Protection of Muslim Families in Conflict Areas: A Criminal Law Study Based on the Maqāṣid al-Syarī‘ah of Imam al-Syāṭibī in Gaza, Palestine - Soleh, Muhamad; Yunus, Nur Rohim; Fachruddin, Imam (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2025)
The protracted armed conflict in Gaza, Palestine, has profoundly affected the survival, security, and resilience of Muslim families. The ongoing war not only threatens their physical safety but also disrupts the social fabric, weakens economic stability, and erodes moral foundations within the family unit. In this context, family protection in conflict zones requires a comprehensive legal framework, one of which can be approached through the Maqāṣid al-Syarī‘ah perspective as articulated by Imam al-Syāṭibī. This study seeks to analyze the concept of Muslim family protection through the lens of maqāṣid principles, assess the dynamics of legal politics in Gaza, and evaluate the role of criminal law in safeguarding families in conflict. Employing a qualitative juridical-normative and sociological method, the research relies on literature studies of regulations, government policies, scholarly works, and international reports. The findings demonstrate that family protection efforts in Gaza partially reflect maqasid values such as hifz al-nafs, hifz al-‘aql, and hifz al-nasl, though they are hindered by limited legislation, weak infrastructure, and political instability. Imam al-Syāṭibī’s thought offers a strong normative foundation for integrating benefit into legal policy, thereby reinforcing family resilience amid crisis.